2011
DOI: 10.1007/s10815-011-9572-2
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of buffalo embryonic stem-like cells from in vitro-produced blastocysts on homologous and heterologous feeder cells

Abstract: Purpose The aim of the present study is to compare the ability of homologous and heterologous embryonic fibroblast feeder layers to support isolation and proliferation of buffalo ES-like cells generated from hatched and expanded blastocysts produced by in vitro fertilization and characterization of derived cells through expression of pluripotent markers. Methods Embryonic stem cells were derived from hatched and expanded blastocysts through intact blastocyst culture and enzymatic method respectively and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 45 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Whereas several earlier studies have indicated the requirement of LIF for the maintenance of buffalo ES celllike cells in an undifferentiated state, the presence of LIF alone is not sufficient for their long-term culture (Verma et al 2007;Anand et al 2011;Kumar et al 2011). We have recently shown that a combination of LIF and bFGF is capable of supporting long-term self-renewal of buffalo ES cell-like cells on BFF feeder-layer support (Sharma et al 2011), indicating that both these signalling pathways are operative in buffalo ES cell-like cells.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas several earlier studies have indicated the requirement of LIF for the maintenance of buffalo ES celllike cells in an undifferentiated state, the presence of LIF alone is not sufficient for their long-term culture (Verma et al 2007;Anand et al 2011;Kumar et al 2011). We have recently shown that a combination of LIF and bFGF is capable of supporting long-term self-renewal of buffalo ES cell-like cells on BFF feeder-layer support (Sharma et al 2011), indicating that both these signalling pathways are operative in buffalo ES cell-like cells.…”
Section: Discussionmentioning
confidence: 98%
“…Studies deriving iPSCs from other species have shown the process is applicable across a wide range of animals. For example, multiple groups have derived iPSCs from dogs, horses, sheep, pigs, goats and other wild species [11][12][13][14][15][16][17][18]. With respect to felids, there are two studies describing the generation of iPSCs from wild species [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The ES-like cells have shown expression of some pluripotency markers, stem cell-specific cell surface antigens and ability of cells to differentiate into other cell types in buffaloes (Verma et al 2007;Anand et al 2011;Kumar et al 2011 have shown expression of key pluripotency genes in the AFderived stem cell-like cells in buffalo. In the present study, the amnion-derived stem cells show comparable expression of key pluripotency genes, namely, NANOG, OCT-4 and SOX-2.…”
Section: Discussionmentioning
confidence: 99%